Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content: 1. Methods of measuring migration - Irbid Governorate as a model Mrs. Ibtisam “Mahmoud Amin” Marie , Prof. Nazih Ibrahim Almanasieh 2. The study of motives and the Issues of Mixed Marriages in Saudi Arabia: An Inductive Analytical Approach in Literature Review Lecturer Munirah A. Alduraywish 3. Situational Awareness towards Enhancing the Quality of Life for Rural Women in Some Villages in Zefta Center, Gharbia Governorate Dr. Rabab Selim Elserafy 4. The sustainability of the types of floors used within the spaces of temporary housing in the Hajj season Mrs. Najwa Nasser Al-Hazmi 5. The criminal and social effects of electronic games "A comparative legal jurisprudence study in the light of Saudi law and Islamic law" Dr. Abdu Ali Muhammad Al-Jedi 6. Evaluation of the Knowledge Sharing Process on the Ministry of Education Website in The Kingdom of Saudi Arabia: A Case Study Dr. Mona Ali Mahnabi 7. Publishing policies in open access journals: A literature review Mr. Fahad Saad Alnasser 8. A Critical Reading of the Major Introductions to understanding the West and its Determinants A systematic attempt to establish the Occidentalism Prof. Abdul Aziz Fodil BOUCHAIR